Dentoskeletal changes of maxillary molar distalization by Distalizador Molar DV-1 appliance (Journal of Hama University, 2020)
This research aims to study the efficiency of Distalizador Molar DV-1 in maxillary molars distalization. The sample consisted of 10 unilateral class II patients who have the maxillary second molars erupted to the occlusal plane. Dentoskeletal changes in those patients were evaluated using cephalometric radiographs.Distalizador Molar DV-1 was able to distalize the maxillary first molars 3.52 mm with distal inclination of 5.48 degree. This distalization wasn’t accompanied with skeletal vertical changes. Also, no sagittal anchorage loss was measured on maxillary second premolars and incisors, but maxillary second premolars were intruded 0.9 mm. No vertical changes were measured on maxillay distalized molars neither maxillary incisors. Distalizador Molar DV-1 was efficient in distalizing maxillary first molars and correcting class II molar relationship despite the presence of maxillary second molars, and no unfavorable anchorage loss was noticed  (P